Mughal–Rajput Relations: Cooperation, Marital Alliances, and Political Consolidation: मुगल–राजपूत संबंध: सहयोग, वैवाहिक गठबंधन और राजनीतिक सुदृढ़ीकरण का ऐतिहासिक परिप्रेक्ष्य - Chamoli, Amit; Veeru (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Mughal–Rajput relations form a very significant aspect of medieval Indian history. Until the mid-16th century, the Mughal Empire was confined to only a few parts of northern India and faced constant challenges. At this time, Akbar realized that to bring stability and a broader base to the empire, it was essential to secure the cooperation of local powers. The Rajputs, known for their valor, military skills, and regional influence, emerged as the most suitable allies. Thus, instead of relying solely on war and suppression, Akbar prioritized a policy of “cooperation and integration.” The most important dimension of this policy was marital alliances, which not only strengthened political cooperation but also promoted social and cultural closeness. The Mughal policy toward the Rajputs stands out in Indian history as an excellent example of cultural synthesis and political pragmatism. These marital alliances not only reinforced the foundations of the empire but also nurtured a new sensitivity and tolerance in Hindu–Muslim relations. Without Rajput support, the Mughal Empire could not have attained such stability and vastness. This policy also provides a historical backdrop to the pluralistic tradition of modern India. Abstract in Hindi Language: मुग़ल और राजपूत संबंध भारतीय मध्यकालीन इतिहास का अत्यंत महत्वपूर्ण पक्ष है। 16वीं शताब्दी के मध्य तक मुग़ल साम्राज्य केवल उत्तरी भारत के कुछ भागों तक ही सीमित था और उसे निरंतर चुनौतियों का सामना करना पड़ रहा था। ऐसे समय में अकबर ने यह समझा कि यदि साम्राज्य को स्थिरता और व्यापक आधार देना है, तो उसे स्थानीय शक्तियों का सहयोग लेना होगा। राजपूत, अपनी वीरता, सैन्य दक्षता और क्षेत्रीय प्रभाव के कारण सबसे उपयुक्त सहयोगी थे। इसीलिए अकबर ने केवल युद्ध और दमन की नीति नहीं अपनाई, बल्कि “सहयोग और समन्वय” की नीति को प्राथमिकता दी। इस नीति का सबसे महत्त्वपूर्ण आयाम विवाह-गठबंधन थे, जिनके माध्यम से राजनीतिक सहयोग के साथ-साथ सामाजिक और सांस्कृतिक निकटता भी बढ़ी। मुग़लों की राजपूत नीति भारतीय इतिहास में सांस्कृतिक समन्वय और राजनीतिक व्यवहारिकता का उत्कृष्ट उदाहरण है। विवाह-गठबंधनों ने न केवल साम्राज्य की नींव को सुदृढ़ किया, बल्कि हिंदू-मुस्लिम संबंधों में भी एक नई संवेदनशीलता और सहिष्णुता उत्पन्न की। राजपूतों के सहयोग के बिना मुग़ल साम्राज्य इतनी स्थिरता और व्यापकता प्राप्त नहीं कर सकता था। यह नीति आधुनिक भारत की बहुलतावादी परंपरा की भी ऐतिहासिक पृष्ठभूमि प्रदान करती है। Keywords: मध्यकालीन इतिहास, मुग़ल–राजपूत संबंध, सत्ता-संतुलन, सांस्कृतिक